Azimuthal anisotropy measurements of strange and multistrange hadrons in U+U collisions at √sNN=193 GeV at the BNL relativistic heavy ion collider - Abdallah, Mohamed Samy; Deppner, Ingo Martin; Herrmann, Norbert; Söhngen, Yannick; Weidenkaff, Philipp (Physical review, 2021)
We present systematic measurements of azimuthal anisotropy for strange and multistrange hadrons (K0s, Λ, Ξ, and Ω) and ϕ mesons at midrapidity (|y|< 1.0) in collisions of U+U nuclei at √sNN=193 GeV, recorded by the STAR detector at the Relativistic Heavy Ion Collider. Transverse momentum (pT) dependence of flow coefficients (v2, v3, and v4) is presented for minimum bias collisions and three different centrality intervals. Number of constituent quark scaling of the measured flow coefficients in U+U collisions is discussed. We also present the ratio of vn scaled by the participant eccentricity (ɛn{2}) to explore system size dependence and collectivity in U+U collisions. The magnitude of v2/ɛ2 is found to be smaller in U+U collisions than that in central Au+Au collisions contradicting naive eccentricity scaling. Furthermore, the ratios between various flow harmonics (v3/v3/22, v4/v4/22) are studied and compared with hydrodynamic and transport model calculations.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Gesehen am 26.07.2021